CATEGORY-CONCEPTUAL FRAMEWORK FOR IMPROVING THE LEGAL MECHANISM OF INDUSTRIAL AND CONSUMER WASTE MANAGEMENT - Radionov, Vadim (SWorld-Ger Conference proceedings, 2024)
The article analyzes various waste management mechanisms that are interconnected and collectively form a single technological cycle. A comparative analysis of the categories "waste management" and "waste technological cycle" is provided. The author substa